2023
DOI: 10.1021/acsnano.3c05011
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Selenium/Human Serum Albumin Nanoparticles for Efficient Targeted Treatment of Parkinson’s Disease via Oral Gavage

Kai Xu,
Peng Huang,
Yixuan Wu
et al.

Abstract: Parkinson's disease (PD) is a neurodegenerative disorder characterized by the degeneration of dopamine (DA) neurons in the midbrain substantia nigra pars compacta (SNpc). While existing therapeutic strategies can alleviate PD symptoms, they cannot inhibit DA neuron loss. Herein, a tailormade human serum albumin (HSA)-based selenium nanosystem (HSA/Se nanoparticles, HSA/Se NPs) to treat PD that can overcome the intestinal epithelial barrier (IEB) and blood− brain barrier (BBB) is described. HSA, a transporter f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…At this toxicity threshold dose, mice exhibited toxic reactions to both Se treatments, but the toxic reactions seen from BSA-SeNPs-treated mice were lower than those in selenomethione-treated mice . In the absence of comparison at toxicity threshold dose (5 mg Se/kg herein), a speculation that HSA/Se NPs would have higher short-term toxicity cannot be excluded, since Xu et al provided strong evidence indicating that HSA/Se NPs were more efficient than BSA-SeNPs or Se yeast in increasing tissue Se levels, including the liver, kidney, heart, lung, spleen, and brain (their Figure 5), and agreed with the consensus that “the accumulation of Se in the body in excess of nutritional requirements can cause great harm to the organism” as stated in their article …”
mentioning
confidence: 91%
See 2 more Smart Citations
“…At this toxicity threshold dose, mice exhibited toxic reactions to both Se treatments, but the toxic reactions seen from BSA-SeNPs-treated mice were lower than those in selenomethione-treated mice . In the absence of comparison at toxicity threshold dose (5 mg Se/kg herein), a speculation that HSA/Se NPs would have higher short-term toxicity cannot be excluded, since Xu et al provided strong evidence indicating that HSA/Se NPs were more efficient than BSA-SeNPs or Se yeast in increasing tissue Se levels, including the liver, kidney, heart, lung, spleen, and brain (their Figure 5), and agreed with the consensus that “the accumulation of Se in the body in excess of nutritional requirements can cause great harm to the organism” as stated in their article …”
mentioning
confidence: 91%
“…However, the low toxicity of BSA-SeNPs could be explained by low Se accumulation at high doses in rodents. Xu et al showed that HSA/Se NPs have a large advantage over BSA-SeNPs and Se yeast in raising tissue Se levels at a supranutritional level (1 mg Se/kg) following a single oral administration, due to HSA receptor mediated intake of HSA/Se NPs . We advise that they should be prudent in arguing for lower toxicity of HSA/Se NPs, in the absence of critical comparisons of both short-term Se accumulation at supranutritional level(s) and short-term Se toxicity at toxicity threshold dose(s).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…They wrote in their comment, “The authors prepared selenium (Se) nanoparticles (NPs) by using human serum albumin (HSA) and suggested that the ‘HSA/Se NPs’ have lower toxicity and higher efficacy than other Se species. The other Se species employed in this article include Se yeast and previously reported SeNPs prepared by using bovine serum albumin (BSA), here referred to as BSA-SeNPs.” We believe that such a statement is inconsistent with the original text . The Abstract in the original text states: “Findings reveal that HSA/Se NPs have lower toxicity and higher efficacy than other selenium species and the ability to overcome the IEB and BBB to enrich DA neurons, which then protect MN9D cells from MPP + -induced neurotoxicity and ameliorate both behavioral deficits and DA neuronal death in MPTP-model mice” .…”
mentioning
confidence: 99%
“…The other Se species employed in this article include Se yeast and previously reported SeNPs prepared by using bovine serum albumin (BSA), here referred to as BSA-SeNPs.” We believe that such a statement is inconsistent with the original text . The Abstract in the original text states: “Findings reveal that HSA/Se NPs have lower toxicity and higher efficacy than other selenium species and the ability to overcome the IEB and BBB to enrich DA neurons, which then protect MN9D cells from MPP + -induced neurotoxicity and ameliorate both behavioral deficits and DA neuronal death in MPTP-model mice” . Because of word limitation, it is impractical to list other selenium species in the abstract of the original text, but there is no description in the original text that HSA/Se NPs have lower toxicity than nano-Se (BSA-Se NPs).…”
mentioning
confidence: 99%